Percent Consonants Correct and Vowels Correct as Predictors of Word-Level Intelligibility in Children: Evidence from 394 Indonesian-Speaking Children - Jumiarti Jumiarti; Rexsy Taruna; Stella Rosalina Phandinata (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Speech intelligibility is a key indicator of children’s communicative competence, yet evidence regarding its phonological predictors in Indonesian-speaking children remains limited. This study investigated the extent to which consonant and vowel accuracy predict word-level intelligibility in Indonesian children. A total of 394 typically developing Indonesian children aged 3-6 years participated. Speech production measures included Percent Consonants Correct (PCC), Percent Vowels Correct (PVC), and word-level intelligibility scores. Statistical analyses comprised descriptive statistics, Mann-Whitney U tests for gender comparisons, Spearman correlations controlling for age, and linear regression. Mean scores were 85.25 (PCC), 87.56 (PVC), and 80.04 (intelligibility). Girls outperformed boys across all three measures. Strong correlations were found between PCC, PVC, and intelligibility, with PCC demonstrating the strongest association. Regression analysis indicated that PCC and PVC together explained 75.8% of the variance in intelligibility, with PCC emerging as the dominant predictor. Consonant accuracy is the primary determinant of intelligibility, although vowel accuracy provides additional predictive value. These findings align with cross-linguistic literature and contribute empirical reference data for Indonesian children, highlighting implications for assessment and intervention in speech-language pathology..